Identification of Cadalene-β-Carboxylic Acid from Barks of Bawang Hutan (Scorodocarpus borneensis Becc.) - Rudi Kartika; Bustanussalam Bustanussalam; Partomuan Simanjuntak (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2012)
One sesquiterpene compound has been isolated and identified out of the ethylacetate extract of bawang hutan (Scorodocarpus borneensis Becc.) barks. The barks were macerated with methanol, and then partitioned with mixture of ethylacetate-water (1:1). Fractionation of the ethylacetate phase by column chromatography gave pure compound. Based on data interpretation from of ultra-violet (UV) spectra, Fourier Transform Infra Red (FT-IR), NMR 1D (1H and13C-NMR); NMR 2D (HMQC, COSY, HMBC), and comparison with literature, the pure isolated compound was determined as sesquiterpene compound, cadalene-β-carboxylic acid, which exhibited LC50 of 42.32 ppm. Keywords: bawang hutan, Scorodocarpus borneensis, Olaceaeae, brine shrimp lethality test.